CYFRA 21-1 predicts the efficacy of nivolumab in patients with advanced lung adenocarcinoma - Hiromichi Shirasu; Akira Ono; Katsuhiro Omae; Kazuhisa Nakashima; Shota Omori; Kazushige Wakuda; Hirotsugu Kenmotsu; Tateaki Naito; Haruyasu Murakami; Masahiro Endo; Takashi Nakajima; Toshiaki Takahashi (Tumor Biology, 2018)
CYFRA 21-1 is a prognostic marker for non–small cell lung cancer. The serum CYFRA 21-1 level is also known as an adjunct for the diagnosis of lung squamous cell carcinoma. This study aimed to examine whether CYFRA 21-1 has predictive implications for nivolumab therapy in patients with advanced lung adenocarcinoma. Of the 79 patients who were treated with nivolumab therapy at the Shizuoka Cancer Center between December 2015 and September 2016, we retrospectively reviewed the data of 50 patients. The patient characteristics were as follows: age <70/≥70 years: 43 (86%)/7; male/female: 31 (62.0%)/19; Eastern Cooperative Oncology Group performance status 0–1/2: 43 (86%)/7; smoking status: no/yes: 18 (36%)/32; epidermal growth factor receptor mutation status negative/positive: 36 (72%)/14; CYFRA 21-1 ≥2.2/<2.2 ng/mL: 28 (56%)/22; carcinoembryonic antigen ≥5/<5 ng/mL: 29 (58%)/21; and number of prior regimens 2–3/≥4: 16 (32%)/34. With a median follow-up of 263.5 (range, 64–352) days, the median progression-free survival was 70 days. The clinical variables investigated using univariate analysis were as follows: age (p = 0.423), carcinoembryonic antigen (p = 0.888), epidermal growth factor receptor mutation status (p = 0.105), performance status (p = 0.968), sex (p = 0.210), number of prior regimens (p = 0.146), CYFRA 21-1 (p = 0.026), and smoking status (p = 0.041). A multivariate analysis identified a serum CYFRA 21-1 level ≥2.2 ng/mL as an independent predictor of a favorable outcome (hazard ratio, 0.44; 95% confidence interval, 0.23–0.85; p = 0.015; median progression-free survival, 155 vs 51.5 days). In conclusion, CYFRA 21-1 might be an independent predictor of outcome for patients with advanced lung adenocarcinoma treated with nivolumab.